Gastrointestinal Malignancies and Venous Thromboembolic Disease: Clinical Significance and Endovascular Interventions - Li, Xin; Partovi, Sasan; Gadani, Sameer; Martin, Charles, III; Beck, Avi; Vedantham, Suresh (Digestive Disease Interventions, 2020)
Gastrointestinal malignancy encompasses a wide range of disease processes. Its incidence and mortality rate rank among the highest of all cancers. Venous thromboembolic disease is a common complication of gastrointestinal malignancy. Anticoagulation remains the first-line therapy. However, for patients who cannot tolerate or have failed anticoagulation, inferior vena cava (IVC) filter placement may be an option. Furthermore, to improve symptom resolution and reduce the severity of postthrombotic syndrome, catheter-directed thrombolysis (CDT) may be an option. Recent randomized trials including the ATTRACT (Acute Venous Thrombosis: Thrombus Removal with Adjunctive Catheter-Directed Thrombolysis) trial have shed new light on the efficacy and safety of CDT and related methods. Overall, the decision to proceed with IVC filter placement or CDT must be individualized.
Keywords: CDT; PCDT; GI cancer; IVC filter; anticoagulation